The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10661-008-0490-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of biomarkers in Nile tilapia (Oreochromis niloticus) to assess the impacts of pollution in Bolgoda Lake, an urban water body in Sri Lanka

Abstract: The present study reports the first analysis of water pollutants in Sri Lankan waters using a suite of biomarkers in Nile tilapia (Oreochromis niloticus) residing in Bolgoda Lake which receives urban, industrial and domestic wastes from multiple sources. The fish were collected from the lake in the dry period (April 2005) and wet periods (September 2005, October 2006) and the levels of biomarkers viz. hepatic ethoxyresorufin O-deethylase (EROD), glutathione S-transferase (GST), metallothioneins, biliary fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 17 publications
(26 reference statements)
2
19
1
Order By: Relevance
“…The hepatic GST activities in the control Nile tilapia used in the present study were higher than the values reported for the control fish used in our earlier study (Pathiratne et al 2009). This may be due to the use of higher temperature condition (30°C) of the assay medium in this study to reflect the natural temperature conditions in the Lake.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…The hepatic GST activities in the control Nile tilapia used in the present study were higher than the values reported for the control fish used in our earlier study (Pathiratne et al 2009). This may be due to the use of higher temperature condition (30°C) of the assay medium in this study to reflect the natural temperature conditions in the Lake.…”
Section: Discussioncontrasting
confidence: 86%
“…The ChE activities in the brain and muscle homogenates of individual fish were determined at 25°C using acetylthiocholine iodide as the substrate following the method of Ellman et al (1961) as described earlier (Pathiratne et al 2008). Microsomal and cytosolic fractions of liver tissues were prepared by differential centrifugation (Pathiratne et al 2009). GST in the liver cytosol fraction was measured at 30°C by following the conjugation of glutathione at 340 nm using 1-chloro-2,4-dinitrobenzene as the substrate (Habig et al 1974).…”
Section: Analysis Of Biomarker Enzymesmentioning
confidence: 99%
“…Nile tilapia (Oreochromis niloticus) which is a widespread food fish species in tropical countries has been suggested as a test species for biomonitoring of aquatic pollution in tropical environments (Gold-Bouchot et al 2006;Pathiratne et al 2009). Objective of this study was to compare the effects of commonly occurring five selected PAHs containing two to four fused aromatic rings viz.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, gastrointestinal and hepatic activities for trypsinlike and chymotrypsin-like peptidases and for β-glucosidase were relatively with low variation among the specimens. This was relevant, since the biochemical parameters such as enzymatic activities were usually affected by the pollutants ( Van der Oost et al 2003;Pathiratne et al 2009;Kuz'mina et al 2013). Thus, before specific comparisons between the two reservoirs, one must point out that these hydrolases are promising biomarker for future studies given the acceptable low intraspecific variations and the easy assaying of their activities with chromogenic or natural substrates.…”
Section: Discussionmentioning
confidence: 99%